2016
DOI: 10.1136/tobaccocontrol-2015-052818
|View full text |Cite
|
Sign up to set email alerts
|

Mining social media data for opinion polarities about electronic cigarettes

Abstract: The organic-against tweets raised public awareness of potential health risks and could aid in preventing non-smokers, adolescents and young adults from using e-cigarettes. Opinion polarities about e-cigarettes from social networks could be highly influential to the general public, especially youth. Further educational campaigns should include measuring their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Approximately 1% of all users in the analytical sample provided data that allowed us to describe the geographic areas in which e-cigarette–related discussions took place in the United States. While this is a small percentage, it is compatible with earlier work [ 25 , 40 ] and represents 36,549 users in the United States. Additionally, we did not have the necessary demographic information (eg, age) of Twitter users to consider population density and age distributions of geographic areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Approximately 1% of all users in the analytical sample provided data that allowed us to describe the geographic areas in which e-cigarette–related discussions took place in the United States. While this is a small percentage, it is compatible with earlier work [ 25 , 40 ] and represents 36,549 users in the United States. Additionally, we did not have the necessary demographic information (eg, age) of Twitter users to consider population density and age distributions of geographic areas.…”
Section: Discussionsupporting
confidence: 88%
“…Twitter has been used in tobacco control research with studies showing how tobacco education campaigns can be informed by monitoring tweets [ 11 , 12 ] and which e-cigarette–related messages are likely to spread on Twitter [ 13 ], among other studies [ 14 - 21 ]. Ayers and colleagues [ 22 ] recently analyzed a sample of e-cigarette–related tweets and reported that social image was the most identified reason for e-cigarette use in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…732,746 ENDS are promoted heavily online 451,695 through ENDS company–sponsored advertisements 697 and users’ social media profiles, 424 with occurrences on YouTube 690,697,706,707,710,722,731,739 and Twitter. 691,713,715,725727,733,743 Youth and young adult exposure to TV advertisements for ENDS has increased since 2011. 689,735 Two RCTs 712,720 and four cross-sectional studies 403,629,723,741 have shown that tobacco marketing exposure may promote ENDS uptake.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Different from the posts from other mainstream social media like Twitter and Reddit, JuiceDB posts are more focused on the e-liquid features [7]. The rich information in the review data and advanced sentiment analytics have made mining and summarizing e-cigarette information from the unstructured texts possible [8]. …”
Section: Introductionmentioning
confidence: 99%